Anterior cervical discectomy and fusion, open-door laminoplasty, or laminectomy with fusion: Which is the better treatment for four-level cervical spondylotic myelopathy? - Zhong, Huajian; Xu, Chen; Wang, Ruizhe; Wu, Xiaodong; Wu, Huiqiao; Sun, Baifeng; Wang, Xinwei; Chen, Huajiang; Shen, Xiaolong; Yuan, Wen (Frontiers in Surgery, 2023)
-level cervical spondylotic myelopathy (CSM) is a common disease suffering large amount of people, with optimal surgical strategy remains controversial. This study compared the clinical outcomes, radiological parameters, and postoperative complications of primarily performed surgical procedures, including anterior cervical discectomy and fusion (ACDF), open-door laminoplasty (LAMP), or laminectomy with Fusion (LF) in treating four-level CSM. 116 patients who received ACDF (38 cases), LAMP (45 cases) or LF (33 cases) and followed up for a minimum of 24 months were enrolled in this study and retrospectively analyzed. Clinical outcomes were evaluated by the Japanese Orthopedic Association (JOA) scoring system, the Neck Disability Index (NDI) and the Visual Analogue Scale (VAS). The changes in curvature of cervical spine were determined by cervical curvature index (CCI) and C2–C7 Cobb angle. The cervical mobility was evaluated using C2–C7 range of motion (ROM) and active cervical ROM (aROM). Complications were recorded and compared between the groups. All patients achieved significant improvement in JOA, NDI and VAS scores at the final follow-up (P<0.05), whereas no remarkable difference was found among groups (P> 0.05). In addition, both C2–7 ROM and aROM reduced significantly in three groups and LAMP showed the least reduction relatively. As for complications, LAMP showed the lowest overall incidence of postoperative complications, and patients in ACDF group were more susceptible to Dysphagia, pseudoarthrosis and revision surgery than LAMP and LF. Considering improvement on clinical symptoms and neurological function, there was no remarkable difference among the clinical efficacy of ACDF, LAMP and LF. Nevertheless, LAMP had advantages of preserving cervical mobility and reducing postoperative complication over the other two surgical procedures.